Antenna Developments for Military Applications - Zaghloul, Amir I.; Weiss, Steven J.; Coburn, W. Keefe (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A review of current, past and projected activities in antenna development indicates a broad spectrum of requirements, and subsequently a variety of innovations to meet these requirements for military radar and communications systems. Designing the antennas in the operating environment, known as in-situ design, is an important factor in guaranteeing the successful operation of the antenna in the field. This paper presents the basic blocks in antenna development, followed by examples of some antennas developed at the Army Research Laboratory for military systems and applications. These include Rotman lenses as beam formers for electronically scanning arrays; phased arrays using MEMS phase shifters at 30 GHz; a 76-GHz narrow beam, low-sidelobe antenna for collision avoidance radar; and other specialized antennas. Of special interest is an effort on developing and using metamaterials in antenna designs, where practical realizations of such materials have the potential of improving the performance and reducing the size of antennas.